Essays in financial economics - BERGANT, KATHARINA (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2019)
This thesis comprises five papers in Financial Economics. The first part contains three essays in International Finance followed by two essays in Empirical Banking. The International Finance chapter focuses on the determinants of international capital flows. It starts with an analysis of the increasing divergence of the net international investment posi- tion in the post-crisis period. By decomposing the change in the net international investment position into capital flows and valuation effects, I show that the increasing stock imbalances are driven by the former. However, valuation changes show a stabilising pattern. Countries with the largest net foreign liabilities experienced the greatest valuation gains. Analysing this effect across different asset classes indicates that this stabilising pattern was driven by a change in the value of portfolio equity. The pro-cyclical movement of domestic stock markets during the post-crisis period improved international risk sharing through foreign portfolio equity liabilities. In the second paper, I take the analysis of valuation effects to the micro level. Martin Schmitz and I use confidential data on security holdings of all euro area investors to review portfolio rebalancing patterns in response to valuation changes. Our empirical findings provide evidence for ?momentum investment" as investors carry out larger net purchases of securities which experience relatively higher valuation gains. For securities denominated in foreign currency (i.e. non-euro), momentum investment is significantly stronger and driven by valuation gains from exchange rate dynamics rather than changes in market prices. The chapter ends with an analysis of international capital flows during the European Central Bank?s (ECB) Asset Purchase Programme in the third essay. We show that euro area investors actively rebalanced away from securities targeted under the ECB?s Public Sector Purchase Programme and other euro-denominated debt securities, towards foreign debt instruments, including ?closest substitutes?, i.e. certain sovereign debt securities issued by non-euro area advanced countries. This rebalancing was particularly strong during the first six quarters of the programme with marked differences across sectors as well as country groups within the euro area, suggesting that quantitative easing has induced heterogeneous portfolio shifts. The second part of the dissertation contains two papers on Empirical Banking that focus on patterns of bank lending to households and firms. In the first paper, Thore Kockerols and I use supervisory loan-level data on corporate loans to show that banks facing high levels of non-performing loans relative to their capital and provisions were more likely to grant forbearance measures to the riskiest group of borrowers. Moreover, we find that none of the forbearance measures significantly reduce the probability of default in the long run. As high shares of forbearance are negatively correlated with new lending to the same group of borrowers, our evidence also suggests that forbearance and new lending are substitutes for banks. In the second paper, my co-authors Viral Acharya, Matteo Crosignani, Tim Eisert, Fergal McCann, and I examine the impact on bank lending and risk-taking of loan-to-income and loan-to-value limits on the issuance of residential mortgages. We show that banks play an important role in the transmission of macroprudential policies aimed at limiting household leverage. In response to these limits, banks reallocate credit from low- to high-income borrow- ers and from counties where borrowers are close to the limits to counties where borrowers are more distant from the limits. This mortgage reallocation is effective in slowing down house price growth in ?hot? housing markets from above 20% to 4% year over year. However, banks try to maintain a stable risk exposure by increasing their risk-taking in asset classes not targeted by the regulation ? such as credit to firms and holdings of securities ? and reallocating mortgage credit to borrowers more likely to default during real estate busts.
APPROVED
Keywords: International finance; Empirical banking